Behavioral Impulsivity Predicts Treatment Outcome in a Smoking Cessation Program for Adolescent Smokers - Krishnan-Sarin, Suchitra (2006)
OBJECTIVE: To examine the relationship between impulsivity and smoking cessation treatment response among adolescents. METHODS: Thirty adolescent smokers participated in a high school based smoking cessation program combining contingency management and cognitive behavioral therapy. Self-report (Barratt Impulsiveness Scale (BIS—11); Kirby Delay Discounting Measure (DDM)) and behavioral (Experiential Discounting Task (EDT); Continuous Performance Task (CPT)) measures of impulsivity were assessed at treatment onset. RESULTS: Sixteen participants (53%) were abstinent from smoking at completion of the four-week study. Compared to abstinent adolescents, those not achieving abstinence discounted monetary rewards more on the EDT and committed more commission errors on the CPT. Group differences were not observed on the BIS-11 or DDM. CONCLUSIONS: These preliminary results suggest that specific behavioral measures of impulsivity may be associated with the ability to initiate and/or maintain abstinence from smoking among adolescent smokers.